Post-Translational Modifications of Proteins Orchestrate All Hallmarks of Cancer - Pathea Shawnae Bruno; Aneeta Arshad; Maria-Raluca Gogu; Natalie Waterman; Rylie Flack; Kimberly Dunn; Costel C. Darie; Anca-Narcisa Neagu (Life)
Post-translational modifications (PTMs) of proteins dynamically build the buffering and adapting interface between oncogenic mutations and environmental stressors, on the one hand, and cancer cell structure, functioning, and behavior. Aberrant PTMs can be considered as enabling characteristics of cancer as long as they orchestrate all malignant modifications and variability in the proteome of cancer cells, cancer-associated cells, and tumor microenvironment (TME). On the other hand, PTMs of proteins can enhance anticancer mechanisms in the tumoral ecosystem or sustain the beneficial effects of oncologic therapies through degradation or inactivation of carcinogenic proteins or/and activation of tumor-suppressor proteins. In this review, we summarized and analyzed a wide spectrum of PTMs of proteins involved in all regulatory mechanisms that drive tumorigenesis, genetic instability, epigenetic reprogramming, all events of the metastatic cascade, cytoskeleton and extracellular matrix (ECM) remodeling, angiogenesis, immune response, tumor-associated microbiome, and metabolism rewiring as the most important hallmarks of cancer. All cancer hallmarks develop due to PTMs of proteins, which modulate gene transcription, intracellular and extracellular signaling, protein size, activity, stability and localization, trafficking, secretion, intracellular protein degradation or half-life, and protein–protein interactions (PPIs). PTMs associated with cancer can be exploited to better understand the underlying molecular mechanisms of this heterogeneous and chameleonic disease, find new biomarkers of cancer progression and prognosis, personalize oncotherapies, and discover new targets for drug development.